Measurement of the c-jet mistagging efficiency in t ¯t events using pp collision data at √s = 13 TeV collected with the ATLAS detector - Aad, G.; Abbott, B.; Abbott, D. C.; Aliev, M.; Kostyukhin, Vadim V.; Kuchinskaya, Olesya I.; Penzin, Maxim S. (The European Physical Journal C)
A technique is presented to measure the efficiency with which c-jets are mistagged as b-jets (mistagging efficiency) using t (t) over bar events, where one of theW bosons decays into an electron or muon and a neutrino and the other decays into a quark-antiquark pair. The measurement utilises the relatively large and known W -> cs branching ratio, which allows ameasurement to be made in an inclusive c-jet sample. The data sample used was collected by the ATLAS detector at root s = 13 TeV and corresponds to an integrated luminosity of 139 fb(-1). Events are reconstructed using a kinematic likelihood technique which selects the mapping between jets and t (t) over bar decay products that yields the highest likelihood value. The distribution of the b-tagging discriminant for jets from the hadronic W decays in data is compared with that in simulation to extract the mistagging efficiency as a function of jet transverse momentum. The total uncertainties are in the range 3-17%. The measurements generally agree with those in simulation but there are some differences in the region corresponding to the most stringent b-jet tagging requirement.